Porcine DNA in Medicine toward Postpartum Patients from Medical and Islamic Perspectives in Malaysia - Siti Nur Syahadah binti Mod Ali; Setiyawan Bin Gunardi (Indonesian Society for Knowledge and Human Development, 2024)
Nowadays, the issue of the use of pig resources in medicine is a disputed Halal and Haram study. The widespread social media exposure of medicines containing pork in Malaysia has raised concern among many people, especially postpartum patients, who often be provided with porkbased medicine to prevent blood clots in the body. Most Malaysians still do not know the real action to take when faced with such a scenario. Thus, this study focuses on the purpose and requirements in using porcine DNA in postpartum patients according to the perspective of Medicine and Islam in Malaysia. This research methodology used qualitative methods through a library research approach by reviewing selected articles and interviews with physicians and Fiqh. The data collected were analyzed based on the principles of Maqasid Al-Shariah and Dharurah. By applying the principle “al-Darurat Tubih al-Mahzurat”, the results found that porcine DNA in medicine are allowed to use toward postpartum patients in Dharurat when there is no other option other than using drugs from haram sources.